2003
DOI: 10.1001/archderm.139.4.510
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Chronic Wounds With Bone Marrow–Derived Cells

Abstract: Background: Recent evidence indicates that bone marrow contains stem cells with the potential for differentiation into a variety of tissues, including endothelium, liver, muscle, bone, and skin. It may thus be plausible that bone marrow-derived cells can provide progenitor and/or stem cells to wounds during healing. Our objective in this study was to establish proof of principle that bone marrow-derived cells applied to chronic wounds can lead to closure of nonhealing wounds. We applied autologous bone marrow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
263
0
10

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 394 publications
(283 citation statements)
references
References 27 publications
(28 reference statements)
10
263
0
10
Order By: Relevance
“…Similarly, as pluripotential stem cells are capable of differentiating into a variety of cell types including fibroblasts and keratinocytes, stem cell therapy may be efficacious in chronic wounds. Preliminary data have suggested that autologous bone marrow cells applied to chronic wounds might accelerate healing [100].…”
Section: Wound Healing and The Importance Of Offloadingmentioning
confidence: 99%
“…Similarly, as pluripotential stem cells are capable of differentiating into a variety of cell types including fibroblasts and keratinocytes, stem cell therapy may be efficacious in chronic wounds. Preliminary data have suggested that autologous bone marrow cells applied to chronic wounds might accelerate healing [100].…”
Section: Wound Healing and The Importance Of Offloadingmentioning
confidence: 99%
“…BM can also generate epithelial cells, i.e., keratinocytes, in the epithelia, although the precise derivations and mechanisms to raise BM-derived keratinocytes are not fully known (3,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Human/mouse studies involving transplantation of sex-mismatched or genetically tagged BM cells have shown that keratin-positive bone marrow-derived cells can be found in skin epidermis, hair follicles, and sebaceous glands (6,8,9,11,12,14,16), sites that harbor skin stem cell niches (17). Moreover, in humans who have undergone BM transplantation (BMT), donor cells that have differentiated into keratinocytes can be detected in the epidermis for at least 3 y (8).…”
mentioning
confidence: 99%
“…1 and 2) and applied ( Fig. 3) as described by Falanga and colleagues 4 Complete wound healing was considered as end point of the study.…”
Section: Methodsmentioning
confidence: 99%